Trade-offs between data resolution, accuracy, and cost when choosing information to plan reserves for coral reef ecosystems - Tulloch, Vivitskaia J.; Klein, Carissa J.; Jupiter, Stacy D.; Tulloch, Ayesha I.T.; Roelfsema, Chris; Possingham, Hugh P. (Journal of environmental management, 2017)
Conservation planners must reconcile trade-offs associated with using biodiversity data of differing qualities to make decisions. Coarse habitat classifications are commonly used as surrogates to design marine reserve networks when fine-scale biodiversity data are incomplete or unavailable. Although finely-classified habitat maps provide more detail, they may have more misclassification errors, a common problem when remotely-sensed imagery is used. Despite these issues, planners rarely consider the effects of errors when choosing data for spatially explicit conservation prioritizations. Here we evaluate trade-offs between accuracy and resolution of hierarchical coral reef habitat data (geomorphology and benthic substrate) derived from remote sensing, in spatial planning for Kubulau District, Fiji. For both, we use accuracy information describing the probability that a mapped habitat classification is correct to design marine reserve networks that achieve habitat conservation targets, and demonstrate inadequacies of using habitat maps without accuracy data. We show that using more detailed habitat information ensures better representation of biogenic habitats (i.e. coral and seagrass), but leads to larger and more costly reserves, because these data have more misclassification errors, and are also more expensive to obtain. Reduced impacts on fishers are possible using coarsely-classified data, which are also more cost-effective for planning reserves if we account for data collection costs, but using these data may under-represent reef habitats that are important for fisheries and biodiversity, due to the maps low thematic resolution. Finally, we show that explicitly accounting for accuracy information in decisions maximizes the chance of successful conservation outcomes by reducing the risk of missing conservation representation targets, particularly when using finely classified data. •We evaluate spatial planning trade-offs from using coral reef habitat data of differing accuracy.•We compare reserves designed using high accuracy geomorphology vs finer detail benthic substrate.•Accounting for mapping accuracy reduces the risk of missing conservation targets.•Using fine habitat classifications with low accuracy leads to larger and more costly reserves.•Coarse classifications are most cost-effective with low data costs and reduced impacts on fishers.